Structure and Nutritional Composition of Fonio (Digitaria exilis) Grains : A Review - BALLOGOU, Vénérande Y. (My University, 2013)
Fonio is a traditional cereal which has often occupied a marginal position among the other cultures, in most of West African countries where it is cultivated, in spite of its cultural, nutritional and economic importance in many socio-cultural groups. Processing and utilization of fonio require adequate knowledge on its structural, chemical and nutritional characteristics which were the purpose of the present review. In this paper, the structure of fonio was reported and compared to the that of other major cereals, such as maize, rice, millet and sorghum. It seems that Fonio starch granules were like rice starches; hence some current applications of rice starch could be applied to that from fonio grains. The chemical and nutrient composition of D. exilis grain was also reviewed. The carbohydrates, protein, lipid, ash and fiber contents of fonio grains reported by various authors and also micronutrients mainly amino acids, fatty acids, minerals and vitamins were presented.
Keywords: Structure; chemical composition; nutritional characteristics; fonio.